HBO, Game of thrones, Mikannn e Carol Moreira: um estudo sobre as relações entre o mercado e a produção de fãs na tv contemporânea - Rezende, Nathalia Michelle Grisi (2017)
This research aimed to analyze the communication phenomenon formed around the strategies of HBO in the release of the TV series Game Of Thrones and the behavior of the fan of this TV series on the social network YouTube. Critical, audience and public success, but being a television product clearly demarcated by broadcasting, Game Of Thrones is used in this dissertation as a clipping to think contemporary television permeated by new logics of production, distribution and spectatoriality. For that purpose, literature reviews on the processes of media convergence, transmission, narrative complexity, puncturability strategies, propagability, and the emergence of a Social TV in a scenario described as a series culture were carried out. The corpus of analysis was composed by the videos broadcast between the fifth and sixth season of the series and during the exhibition of the sixth, by the official channel of HBO in Brazil and the unofficial channels Mikann and Carol Moreira. The analysis was carried out around three axes: the analysis of the videos conveyed by HBO on the series; The analysis of the videos produced unofficially by the channels Mikann and Carol Moreira; And analysis of the relations created from the official channel and the unofficial channels. The analytical approach and categorization of videos and practices took into account the content of the videos. The results indicated that the strategies employed by HBO broaden the fan experience of the series and serve as a feedback engine for new content to be created for the universe, which in turn serve the purpose of advertising.